Composition and physiological roles of gut microbiota in the False Coding Moth (Thaumatotibia leucotreta) - Richardson, Perryn Heather (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Gut microbiota can have a profound influence on host performance, behaviour and fitness. For False Codling Moth (FCM), Thaumatotibia leucotreta (Lepidoptera: Tortricidae), a major pest of citrus in South Africa, little work has been undertaken to date on gut microbe diversity or its influence on the host. This thesis aimed to i) characterise the gut microbiome of FCM under laboratory conditions and in FCM from the field, ii) and produce moths with reduced gut microbiota through egg dechorionation, which was followed by iii) the measurement of a suite of physiological traits, namely mass, survival and thermal stress in FCM from normal laboratory, dechorionated laboratory and field collected larvae that may be indicative of overall field performance. We aimed to directly test the hypothesis that gut microbial diversity partly determines insect performance and fitness by measuring its effects on growth, development, and tolerance to cold temperatures in FCM. FCM eggs that underwent dechorionation with sodium hypochlorite had an overall effect on larval survival, egg morphology and both larval and adult moth physiological measures. Increasing concentrations of sodium hypochlorite significantly decreased insect survival, (ð œ’2(1, n = 10 850) = 21.724, p-value < 0.0001), with a concentration of â‰ˆ3.69% as the concentration limit (p-value < 0.001). Successful dechorionation of FCM was achieved with a wash of sodium hypochlorite at around 3.69% concentration and was visually confirmed by reduction of FCM egg surface area, (ð œ’2(25, n = 260) p-value < 0.0001) and Scanning Electron Micrographs of the egg morphology. The gut microbiome of FCM from the different focus treatments was successfully characterized. Identification of the dominant bacterial families in these microbiomes revealed Xanthobacteraceae, Beijerinckiaceae and Burkholderiaceae in both the laboratory reared and field collected larvae, which suggests their systematic association with T. leucotreta. The most abundant genera were revealed as Bradyrhizobium, Methylobacterium and Burkholderia-Caballeronia-Paraburkholderia. Comparison of larval mass showed that treatment (dechorionated or not) had a significant effect on larval mass (ð œ’2(2, n = 230) = 22.703, p-value < 0.001), field larvae were heavier than both control larvae and larvae with a disrupted gut microbiome. However, adult insects with a disrupted gut microbiome had more mass than individuals from the control and field-collected larvae with intact gut microbiomes (ð œ’2(2, n = 230) = 39.074, p-value < 0.001). Despite the difference in mass between larval treatments, there was no significant difference in relative protein (ð œ’2(2, n = 24) = 5.680, p-value = 0.06), carbohydrate (ð œ’2(2, n = 24) = 3.940, p-value = 0.14) or lipid (ð œ’2(2, n = 24) = 6.032, p-value = 0.05) content between individuals from the control and dechorionated treatments and field-collected individuals. Turning to thermal physiology, insects collected from the field took significantly longer to recover from chill coma than both laboratory treatments with intact and disrupted gut microbiomes (ð œ’2(2, n = 129 = 39.659, p-value < 0.001). In addition, exposure to cold stress showed that treatment had a significant effect on insect mortality (ð œ’2(2, n = 272) = 9.176, p-value = 0.01), with individuals from the control and dechorionated treatment being less likely to die after experiencing cold stress compared to field-collected individuals. Differences in the mass and thermal tolerance of insects with intact and disrupted gut microbiota suggest that gut microbiota may play an important role in the cold performance of T. leucotreta, and these findings constitute the basis for future molecular work on the functions of these bacterial taxa. This research highlights the need for consideration of the effects of T. leucotreta microbiome in current pest control programs.
Keywords: False codling moth; Microbiomes; Insect physiology; Citrus Diseases and pests -- South Africa; Biological pest control; Cryptophlebia leucotreta